Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1987
DOI: 10.1161/01.str.18.2.490
|View full text |Cite
|
Sign up to set email alerts
|

Identification and quantitative analysis of hydroxy-eicosatetraenoic acids in rat brains exposed to regional ischemia.

Abstract: To clarify possible roles in the pathogenesis of ischemic brain edema, identification and quantitative analysis of hydroxy-ekosatetraenoic acids (HETEs) in rat brains exposed to middle cerebral artery occlusion were carried out using high-performance liquid chromatography. Rat brain sampling was done by in situ freezing 24 and 72 hours after occlusion. Only a small amount of 15-HETE was found in control rat brains. Twenty-four hours after ischemia, 11-HETE appeared, and the amount of 15-HETE tended to increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
22
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 35 publications
(10 reference statements)
3
22
0
Order By: Relevance
“…The present study confirmed previous reports of increased AA-derived prostaglandins (in particular PGE 2 and PGD 2 ), thromboxane B2 and lipoxygenase products (HETE, oxo-ETE and leukotrienes) 41, 46, 47, 56, 70 , and increased DHA-derived 17-HDoHE 41, 49 in hippocampus or whole brain of rodents subjected to hypoxic or ischemic brain injury. By incorporating an expanded AA and DHA oxylipin panel in our LC-MS/MS platform, we also found an increase in epoxidized metabolites of AA and DHA following ischemia in cortex, hippocampus, cerebellum and brainstem.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The present study confirmed previous reports of increased AA-derived prostaglandins (in particular PGE 2 and PGD 2 ), thromboxane B2 and lipoxygenase products (HETE, oxo-ETE and leukotrienes) 41, 46, 47, 56, 70 , and increased DHA-derived 17-HDoHE 41, 49 in hippocampus or whole brain of rodents subjected to hypoxic or ischemic brain injury. By incorporating an expanded AA and DHA oxylipin panel in our LC-MS/MS platform, we also found an increase in epoxidized metabolites of AA and DHA following ischemia in cortex, hippocampus, cerebellum and brainstem.…”
Section: Discussionsupporting
confidence: 93%
“…The majority of unesterified AA and DHA are re-esterified into the phospholipid membrane 44 , whereas a small portion (~3%) is converted via non-enzymatic or enzymatic pathways into oxylipins 41, 45–47 that regulate the brain’s response to injury 2–4 . This response involves oxylipins that acutely down-regulate neuronal hyperexcitability 48 and enhance vasodilation 49 as a protective mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…This difference may be ascribed to the absence of cydooxygenase inhibition. Further, following permanent MCA occlusion in rats, 38 we have shown an enhanced lipoxygenase activity of brain microvessels, which may be triggered by an increase in the ambient level of lipid hydroperoxides. 39 - 41 The possible roles of hydroperoxides and lipoxygenase products in the pathogenesis of edema formation merits further investigation.…”
mentioning
confidence: 65%
“…The free fatty acids contribute to neuronal damage by serving as substrates for the formation of lipid peroxides that have detrimental effects on cellular metabolism and oxygen utilization (314–316). Other fatty acids released during ischemia, such as AA, are converted to HETEs, leukotrienes and eicosanoids (317–319) that compromise collateral flow, increase the production of free radicals (208) and recruit leukocytes in the ischemic area. The recruitment of leukocytes and swelling of the brain may also reduce flow to the injured tissue at the margins of the infarct.…”
Section: 20-hete In Stroke and Traumatic Brain Injurymentioning
confidence: 99%